To factor the expression \( x^3 + 125y^3 \), we recognize it as a sum of cubes. The formula for factoring a sum of two cubes \( a^3 + b^3 \) is:
\[ a^3 + b^3 = (a + b)(a^2 - ab + b^2) \]
In this case, we can identify:
- \( a = x \)
- \( b = 5y \) (since \( 125y^3 = (5y)^3 \))
Applying the sum of cubes formula:
- \( a + b = x + 5y \)
- \( a^2 = x^2 \)
- \( ab = x(5y) = 5xy \)
- \( b^2 = (5y)^2 = 25y^2 \)
Now we can assemble the factors:
\[ x^3 + 125y^3 = (x + 5y)(x^2 - 5xy + 25y^2) \]
So the correct factored form of \( x^3 + 125y^3 \) is:
\[ (x + 5y)(x^2 - 5xy + 25y^2) \]
Thus, the correct option is:
\[ \text{(x + 5y)(x² - 5xy + 25y²)} \]